Avaliação dos efeitos antioxidante, antimicrobiano e antibiofilme de extratos de Hymenaea courbaril (Jatobá) e caracterização química por UPLC-ESI-QTOF-MS/MS - Cruz, Jhonatas Emílio Ribeiro da (2024)
Biofilm-forming bacteria are difficult to treat due to resistance to conventional antibiotic therapy and, therefore, have become a clinical and epidemiological problem worldwide. Furthermore, substantial evidence indicates a vital role for reactive oxygen species (ROS) and other oxidants in cellular metabolism, as responsible for various disorders and pathological conditions. Natural antioxidants, in the form of crude extracts or their chemical constituents, are very effective in preventing harmful processes caused by oxidative stress. Medicinal plants have been identified as possible treatment alternatives due to their antioxidant, antimicrobial and antibiofilm effects. In this context, the present study aimed to determine the content of total phenolic compounds, antioxidant capacity, antimicrobial and antibiofilm potential of nine extracts of the Hymenaea courbaril plant, popularly known as Jatobá. Furthermore, extracts that exhibited promising results (p<0.001 compared to chloramphenicol) of biofilm inhibitory activity against Staphylococcus aureus (ATCC25923) were selected for UPLC-HRMS/MS chemical analysis. The leaves, fruit peel (exocarp) and seeds of the plant were extracted with 96% ethanol using three extraction methods, static maceration (ES), ultrasonic bath (US) and magnetic stirring (AM). The extract from the fruit peel (exocarp) of Jatobá USJC revealed a higher amount of total phenolic compounds (736.1 mg EAG g-1) by the Folin-Ciocalteu test and the extract from the leaves of Jatobá ESJF demonstrated greater antioxidant potential through the test of phosphomolybdenum with a value of (1195.5 mg EBHT g-1). The qualitative antimicrobial activity screening test showed an effect for the nine extracts tested at 500 mg/mL against the pathogenic bacteria S. aureus (ATCC25923) with inhibition halos ranging from 14-17 mm. The Jatobá ESJF leaf extract presented the lowest minimum inhibitory concentration (MIC) of 1.56 mg/mL and also stood out with the best biofilm inhibition, with an inhibition percentage of 78.29%, statistically similar to the chloramphenicol standard (inhibitory effect of 78.85%) (p < 0.001). UPLC-HRMS/MS analysis of leaf extracts (ESJF, USJF and AMJF) of H. courbaril showed the presence of compounds that had not been previously reported in this species, including chrysoeriol-7-O-neohesperidoside, isoramnetin-glucoside, luteolin , rutin, 3,7-di-O-methylquercetin and myricetin. Therefore, these results are promising, indicating the use of H. courbaril as an antioxidant and pointing to its use in antimicrobial therapy with a possible antibiofilm effect.